أسلوب التقديم والتأخير في القرآن الكريم وطريقة تعليمه: The Rhetorical Device of Foregrounding and Backgrounding in the Qur’an and Its Pedagogical Approaches - Alfatawi, Ahmad Talkhis; Ghifari, Ali Al (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2025)
This study examines the phenomenon of taqdīm wa ta’khīr (foregrounding and backgrounding) in the Qur’an and explores effective approaches to teaching this rhetorical device. Employing a qualitative descriptive method within a library research design, the study draws on the Qur’an as the primary source of data, supported by classical and contemporary works in Arabic linguistics and rhetoric. Data were collected through documentation and analyzed using the Miles and Huberman model, including data reduction, display, and conclusion drawing. The findings reveal that taqdīm wa ta’khīr is widely employed in the Qur’an for various rhetorical purposes, most prominently for specification (ikhtiṣāṣ), emphasis (ihtimām), guidance (irshād), and stylistic effect. These variations contribute significantly to the semantic depth and aesthetic quality of Qur’anic discourse. In terms of pedagogy, the study proposes a structured instructional model that includes understanding rhetorical intent, selecting key linguistic elements, introducing concepts progressively, reinforcing through repetition, and utilizing audiovisual aids to enhance comprehension. This study contributes to bridging the gap between Arabic rhetorical theory and its practical teaching, particularly in the context of Qur’anic stylistics.